Prevalence and factors associated with severe fatigue 2 years into the COVID-19 pandemic: a cross-sectional population-based study in Geneva, Switzerland - Silvia Stringhini; Idris Guessous; C Martinez; A Flahault; S Hurst; N Vuilleumier; L Kaiser; K M Posfay-Barbe; O Zimmermann; S Stringhini; A Uppal; P Schaller; et al. (BMJ Open)
Objectives This study aims (1) to assess the prevalence of severe fatigue among the general population of Geneva, 2 years into the COVID-19 pandemic and (2) to identify pandemic and non-pandemic factors associated with severe fatigue.Design Cross-sectional population-based survey conducted in Spring 2022.Setting General adult population of Geneva, Switzerland.Participants 6870 adult participants, randomly selected from the general population, included in the Specchio-COVID-19 cohort study, were invited to answer an online health survey.Outcome and cofactor measure Prevalence of severe fatigue was measured by the Chalder Fatigue Questionnaire with a cut-off score≥4 out of 11. We assessed prevalence ratios of severe fatigue considering sociodemographic factors, health and behavioural characteristics (body mass index, depression, recent diagnosis of chronic disease or allergy, acute health event, smoking status, physical activity and sleep quality) and recent self-reported COVID-19 infections.Results A total of 4040 individuals participated (participation rate 59%, 58% were women, mean age 53.2 (SD=14.1 years)). Overall prevalence of severe fatigue was 30.7% (95% CI=29.2%–32.1%). After adjusting for age, sex, educational level and pre-existing comorbidities, the following characteristics were associated with severe fatigue: individuals aged 18–24 years (adjusted prevalence ratio (aPR)=1.39 (1.10–1.76)) and 25–34 years (aPR=1.23 (1.05–1.45)), female sex (aPR=1.28 (1.16–1.41)), depression (aPR=2.78 (2.56–3.01)), occurrence of health events unrelated to COVID-19 (aPR=1.51 (1.38–1.65)) and self-reported COVID-19 infection in the past 12 months (aPR=1.41 (1.28–1.56)). After further adjustment for depression, previous associations were maintained except for young age.Conclusions About one-third of the adult general population of Geneva experienced severe fatigue, 2 years into the COVID-19 pandemic. Heightened fatigue among young adults is partly explained by depressive symptoms. Recent COVID-19 infection is substantially associated with severe fatigue, regardless of infection severity or co-occurrence of depressive disorder.Trial registration number CCER project ID 2020-00881.